Lite-On of Taiwan : towards a leading global technology corporation - Tang, Hung Kei (2013)
This case study traces the development of Taiwan's first listed electronics company Lite-On Technology Corporation during the period 2000 to 2002. Established in 1975, the founders saw the growth potential in the global PC market and decided to expand into the PC peripheral products market in the late 70's. The strategy of riding on the wave of rapid global PC growth had paid off. Lite-On has become one of the most prominent Taiwanese semiconductor and information technology (IT) firms in terms of revenue and world market share of its key products. Period covered 2000 – 2003